Kindness to animals and spending on them in Islamic jurisprudence (NTU journal for Administrative and Human Sciences (JAHS), 2023)
This Research Aims to Explain The jurisprudential ruling onanimal maintenance and its impact on Islamic jurisprudence andfollow the importance of research by highlighting the legalrooting, Islam looks at the animal world in general with greatinterest due to its importance in life and its cooperation in thebenefit of man, standing on important chapters from the chaptersof jurisprudence, which are the chapters related to the humanrelationship with animals from the expense and treatment, and thestatement of the prohibition and criminalization of Islam to attackand harm animals, and it included a number of conclusions that Iwas able to reach after studying the subject and knowing it in allits aspects - within the limits of the Researcher's knowledge andthe breadth of the papers of the Research raised.